Prinsip Al-'Adl dan Musyawarah Dalam Supervisi Akademik: Analisis di Pondok Modern Darussalam Gontor - Nawawi, Riswandha Ipnu; Astuti, Vera; Subandi, Subandi; Dermawan, Oki (LP2M Universitas Islam Ahmad Dahlan, 2025)
Effective academic supervision focuses not only on the technical-pedagogical aspects, but also on the values ​​and ethics of the process. This study aims to analyze the practice of academic supervision at the Darussalam Gontor Modern Islamic Boarding School through the lens of two fundamental Islamic principles: Al-'Adl and Musyawarah. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with supervisors and supervised teachers, and documentation studies. The research findings indicate that the Al-'Adl principle is manifested in the form of: (1) objectivity in assessment based on clear and transparent criteria; (2) equal treatment regardless of teacher background; and (3) providing proportional and balanced feedback between strengths and areas of improvement. Meanwhile, the Musyawarah principle is implemented through: (1) a dialogic supervision process, where teachers are given space to express their opinions and difficulties; (2) collective discussion of teaching improvement solutions; and (3) final decision-making that takes into account input from the teachers concerned. This study concludes that the integration of Al-'Adl and Musyawarah values ​​in academic supervision creates an environment that emphasizes not only control, but also development (tarbiyah), empowerment, and trust.